Interactive fuzzy random two-level linear programming based on level sets and fractile criterion optimization - Sakawa, Masatoshi; Matsui, Takeshi (Information sciences, 2013)
In this paper, assuming cooperative behavior of the decision makers, two-level linear programming problems under fuzzy random environments are considered by introducing α-level sets of fuzzy random variables and defining an α-stochastic two-level linear programming problem for guaranteeing the degree of realization of the problem. Through a new decision making model proposed based on the fractile criterion optimization model considering fuzzy goals, the α-stochastic two-level programming problem can be equivalently transformed into a deterministic problem. Interactive fuzzy programming to derive a satisfactory solution for the decision maker at the upper level in consideration of the cooperative relation between decision makers is presented. An illustrative numerical example is provided to demonstrate the feasibility and efficiency of the proposed method.